Determining factors to implementing IFRS for SMES: a study in International Accounting Standards Board countries - Zaenal Fanani; Angesthy Puji Rahayu; Angga Erlando (Cogent Business & Management, 2024)
This study aims to obtain empirical evidence regarding the effect of education level, the existence of other accounting standards, and the level of internationality on the application of International Financial Reporting Standards (IFRS) for Small and Medium Enterprises (SMEs) in countries registered with the International Accounting Standards Board (IASB). This study uses a quantitative approach with a research data population of 167 countries registered with the International IASB 2020. The sample data for this study were 101 countries which were selected based on the purposive sampling method. Hypothesis testing in this study uses Logistic Regression Analysis. The results of this study indicate that the level of education and the existence of other accounting standards have a negative effect on the implementation of IFRS for SMEs, while the level of internationality has no significant effect on the implementation of IFRS for SMEs. This study has limitations that lie in the lack of information regarding the timing of the adoption of IFRS for SMEs and the changing number of adopting countries.
Keywords: 650; IFRS for SMEs; neo-institutional theory; institutional isomorphism; mimetic isomorphism and coercive pressure